FRI0083 Reduced increase of ACPA IGG-FC galactosylation during pregnancy in comparison to total IGG: an explanation why autoantibody positive RA-patients improve less during pregnancy?. (15th June 2017) - Bondt, A; Hafkenscheid, L; Falck, D; Kuijper, TM; Rombouts, Y; Hazes, JM; Wuhrer, M; Dolhain, RJ
Abstract : Background: Rheumatoid arthritis (RA) disease activity (DAS28-CRP) improves less during pregnancy in autoantibody positive patients. 1 The most specific autoantibodies for RA are anti-citrullinated protein antibodies (ACPAs), which mainly occur as the immunoglobulin (Ig) G isotype. An association with DAS28-CRP and the pregnancy-associated improvement is well established for the Fc glycosylation of total IgG, in particular for galactosylation (Gal) and sialylation (SA). 2 The Fc glycosylation of ACPAs – mainly present as IgG – has been reported to be different from the total IgG Fc glycosylation. 3 Objectives: We sought to determine whether the change in ACPA IgG glycosylation during pregnancy is different from that of total IgG, and whether this relates to the improvement of RA during pregnancy. Methods: ACPA positive patient sera ( n =152) were obtained within the framework of the PARA cohort, a prospective study designed to investigate pregnancy-associated improvement of RA. ACPA IgG was isolated using microscale affinity chromatography. Trypsin digested ACPA IgG was measured using nano-liquid chromatography mass spectrometry, and compared to total IgG. Results: Pregnancy-associated changes in the levels of glycosylation were observed for all ACPA IgG subclasses. Pregnancy-associated glycosylation changes were less pronounced during pregnancy and after delivery in ACPA IgG (Gal +5%; SA +0.5%) compared to total IgG (Gal +11%; SA +2.5%; Figure 1 ), but – for total IgG – not different between ACPA+ and ACPA- patients. No association of the change in DAS28-CRP with the change in ACPA IgG or total IgG galactosylation was observed for ACPA+ patients, whereas a strong association of total IgG galactosylation was observed for ACPA- patients. Conclusions: During pregnancy the increase in galactosylation of ACPA IgG was less pronounced than that of total IgG, whereas the increase in the galactosylation of total IgG was not different between ACPA+ and ACPA- patients. Since it is known that changes in IgG galactosylation are associated with improvement of RA during pregnancy and since ACPA is thought to be of pathogenic significance in RA, our data might provide an explanation why ACPA+ RA patients are less likely to improve during pregnancy. References: Ince-Askan H, Hazes JM, Dolhain RJ. Identifying clinical factors associated with low disease activity and remission of rheumatoid arthritis during pregnancy. Arthritis Care Res (Hoboken) 2016 doi: 10.1002/acr.23143. Bondt A, Selman MHJ, Deelder AM, et al. Association between galactosylation of immunoglobulin G and improvement of rheumatoid arthritis during pregnancy is independent of sialylation. Journal of Proteome Research 2013;12(10):4522–31. doi: 10.1021/pr400589m. Scherer HU, van der Woude D, Ioan-Facsinay A, et al. Glycan profiling of anti-citrullinated protein antibodies isolated from human serum and synovial fluid. Arthritis Rheum 2010;62(6):1620–29. doi: 10.1002/art.27414. Acknowledgements: This project is funded by the Dutch Arthritis Foundation (NR 10–1-411) and by the European Union's Seventh Framework Program (FP7-Health-F5–2011) under grant agreement no°278535 (HighGlycan). We thank Dr Jan Wouter Drijfhout (LUMC, Leiden) for providing the CCP2 peptide. Disclosure of Interest: None declared